MANAGEMENT OF THE HEAD OF MADRASAH IN IMPROVING TEACHER PERFORMANCE (SURVE AT MIN CITY OF JAMBI) - Suyanto Suyanto (Dinasti Publisher, 2021)
In today's world of education, there is a lot of competition. The output produced by the school must be in accordance with the national education goals. The principal as a manager plays an important role in realizing these goals. In addition, teachers are also expected not only to transfer knowledge but also to be able to provide maximum performance. In order for the teacher to achieve maximum performance, it must be determined through the main tasks of each personnel. This study aims to determine how the level of the principal's management function and teacher performance. Researchers used a qualitative-naturalistic approach. With this concept, the researcher strives for the presence of the researcher not to change the situation or behavior of the person being studied. The method in collecting data in the field is the method of observation, interviews and documentation.